Measurement of Reliability and Construct Validity of Intensification of Job Demands Scale - Grace Odilia; Rezki Ashriyana Sulistiobudi (Journal Research of Social Science, Economics, and Management, 2026)
The presence of a pandemic outbreak has caused continuous changes in work systems, ranging from working from the office to working from home and eventually adopting hybrid work systems. Changes in work systems have also generated organizational changes that affect the emergence of new work demands experienced by employees. The Intensification of Job Demands Scale (IJDS) is a measurement instrument developed by Kubicek and colleagues (2015) to assess the intensification of work demands experienced by employees. This study aimed to evaluate the reliability and construct validity of the IJDS instrument, which had been adapted into Indonesian while considering the cultural context of employees in Indonesia. The participants in this study consisted of 213 employees. The reliability analysis indicated that the measurement instrument demonstrated good reliability. Through discriminant item analysis, one item was removed due to inadequate item discrimination. Content validity was assessed using the Scale-Content Validity Index (S-CVI), which produced a score above 0.80. Confirmatory Factor Analysis (CFA) was conducted, and the results indicated that the items in the measurement instrument demonstrated a good fit with the proposed measurement model. The findings showed that the IJDS instrument was reliable and valid for measuring the intensification of job demands experienced by employees in Indonesia.